Inconsistencies in controlling for risk factors for osteochondral allograft failure: a systematic review - Hailey P. Huddleston; Navya Dandu; Blake M. Bodendorfer; Jared T. Silverberg; Brian J. Cole; Adam B. Yanke (Elsevier, 2022)
Background: As the popularity of Osteochondral allograft (OCA) transplantation increases, studies have commonly investigated potential risk factors that may influence OCA transplantation survivorship. Objectives: To investigate which risk factors of OCA transplantation failure have been evaluated, which have been found to be significant, and the frequency of inclusion of identified risk factors. Data sources: EMBASE, OVID, and Medline Study eligibility criteria: Studies investigating failure after OCA transplantation comparing or investigating one or more risk factors for failure through any statistical approach. Study appraisal and synthesis: All investigated failure risk factors and associated statistical significance were extracted and tabulated by study. The frequency of significance of each factor and inclusiveness of risk factor analysis by each study were assessed. Results: A total of 15 studies were included for qualitative analysis. Age, sex, body mass index (BMI), previous surgeries, and lesion location were among the most frequently investigated variables. Only BMI and previous surgeries were significant in more than one study. Limitations: There was heterogeneity in surgical techniques and varying definitions of failure utilized by each study, making a direct comparison difficult. Conclusions and implications of key findings: OCA failure risk factor analyses are limited primarily to basic demographic factors (eg, age, sex). Furthermore, only 2 identified risk factors were significant in more than one study, limiting the ability to make evidence-based decisions with the current data available. This information could impact operative planning, the decision to perform an OCA over other cartilage restoration procedures, and patient expectations. Systematic review registration number: CRD42021282852